Framing The Energy Crisis: An Analysis of CNN’s Media Hegemony in EU Energy Crisis Coverage - Ering, Maurits Bhoas; Purnama, Chandra; Sari, Deasy Silvya (Ilomata International Journal of Social Science, 2025)
This study analyzes CNN’s framing of the European Union (EU) energy crisis (2022–2025), shaped by the REPowerEU initiative and Russia’s invasion of Ukraine. It fills a gap in international media studies by examining how global news outlets construct hegemonic narratives around energy geopolitics. Using Robert N. Entman’s four-element framing model and Savaş Çoban’s (2018) seven dimensions of media hegemony, the study employs a qualitative interpretivist approach to 30 CNN articles. The findings reveal a consistent framing that attributes the crisis to Russian aggression, portrays the EU as morally resilient, and advances technocratic, market-oriented remedies aligned with neoliberal orthodoxy, while marginalizing oppositional voices, social inequalities, and non-Western perspectives. Theoretically, the research contributes by bridging framing analysis with a critical perspective on media hegemony. Practically, it demonstrates how mainstream media legitimizes specific policy paths while constraining alternatives, thereby reinforcing Western geopolitical dominance. These insights highlight the political power of media framing in shaping global understandings of crisis and governance.